Fibrin Reaction after Uveitic Cataract Surgery: Treatment and Prevention. Issue 4 (July 2014) - da Rocha Lima, Breno; Pichi, Francesco; Nucci, Paolo; Srivastava, Sunil K.; Lowder, Careen Y.
Purpose: To describe the management with intracameral recombinant tissue plasminogen activator (rtPA) of severe fibrin effusion after phacoemulsification, and its prevention with sustained-release dexamethasone intravitreal implant. Methods: A 59-year-old man with chronic HLA-B27–associated uveitis underwent phacoemulsification followed by a sustained-release dexamethasone intravitreal implant. Results: A postoperative severe fibrin reaction was completely resolved after intracameral injection of rtPA. At the time of the phacoemulsification of the fellow eye, a dexamethasone implant was injected 5 days prior to surgery, with no fibrin formation. Conclusions: Intracameral rtPA may be successfully used in the management of severe fibrin reaction. Dexamethasone intravitreal implant to control postoperative inflammation may take several days until it achieves high concentrations in the vitreous.